2023
DOI: 10.3390/molecules28083351
|View full text |Cite
|
Sign up to set email alerts
|

The Large Molecular Weight Polysaccharide from Wild Cordyceps and Its Antitumor Activity on H22 Tumor-Bearing Mice

Abstract: Cordyceps has anti-cancer effects; however, the bioactive substance and its effect are still unclear. Polysaccharides extracted from Cordyceps sinensis, the fugus of Cordyceps, have been reported to have anti-cancer properties. Thus, we speculated that polysaccharides might be the key anti-tumor active ingredients of Cordyceps because of their larger molecular weight than that of polysaccharides in Cordyceps sinensis. In this study, we aimed to investigate the effects of wild Cordyceps polysaccharides on H22 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Furthermore, high molecular weight polysaccharides extracted from Cordyceps sinensis not only enhance the immune function of mice but also induce tumor cell apoptosis through the Cytochrome-c/Caspase8/3 and IL-10/STAT3/Bcl2 pathways, thereby exerting anti-tumor effects [ 33 ]. In H22 hepatocellular carcinoma tumor-bearing mouse models, Ulva lactuca polysaccharide (UIP) extracted from green algae inhibits tumor growth by modulating gut microbiota and metabolite composition.…”
Section: Nps With Therapeutic Activity For Liver Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, high molecular weight polysaccharides extracted from Cordyceps sinensis not only enhance the immune function of mice but also induce tumor cell apoptosis through the Cytochrome-c/Caspase8/3 and IL-10/STAT3/Bcl2 pathways, thereby exerting anti-tumor effects [ 33 ]. In H22 hepatocellular carcinoma tumor-bearing mouse models, Ulva lactuca polysaccharide (UIP) extracted from green algae inhibits tumor growth by modulating gut microbiota and metabolite composition.…”
Section: Nps With Therapeutic Activity For Liver Cancermentioning
confidence: 99%
“…One study found that the polysaccharide from wild Cordyceps significantly inhibited tumor growth and metastasis in H22 tumor-bearing mice, improved blood routine indicators, increased the thymus index, decreased the spleen index, and increased the proportion of CD4+ T cells, CD8+ T cells, and macrophages. It exhibited significant anti-tumor activity by enhancing host immune function [ 33 ]. Furthermore, a polysaccharide (ESPS) purified from Eupolyphaga sinensis Walker promoted lymphocyte proliferation and inhibited liver cancer cell growth by enhancing lymphocyte activity in vitro, primarily natural killer (NK) cells.…”
Section: The Main Action Pathway and Potential Mechanism Of Natural C...mentioning
confidence: 99%
“…Moreover, a liver cancer model of H22 tumor-bearing mice was conducted to determine the anti-cancer effect and underlying mechanism of wild Cordyceps polysaccharides. Multiple experimental means of molecular biological uncovered that the anti-tumor mechanism of the large molecular weight polysaccharide from wild Cordyceps may be related to improving immune function and promoting the apoptosis of tumor cells [89]. WSG, a glucose-rich and water soluble polysaccharide isolated from Ganoderma lucidum, exhibited an anti-tumor effect on Murine Lewis lung carcinoma cell (LLC1)-induced lung cancer mice.…”
Section: Biological Functions 41 Anti-tumor Activitymentioning
confidence: 99%
“…1,2 Several studies have revealed that the extracts of C. sinensis can inhibit tumor cell growth. 3,4 Polysaccharides are the major pharmacologically active compounds of C. sinensis 5,6 and can improve immunity by stimulating immune cell function. 7 In addition, the polysaccharide fraction of C. sinensis can significantly inhibit the proliferation of HCT116 cells and other tumor cell lines, 8−10 eliciting antitumor immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…sinensis can inhibit tumor cell growth. , Polysaccharides are the major pharmacologically active compounds of C. sinensis , and can improve immunity by stimulating immune cell function . In addition, the polysaccharide fraction of C.…”
Section: Introductionmentioning
confidence: 99%